Dar voz ao aluno do supletivo: mudanças pessoais e suas razões - Ferrari, Shirley Costa (2001)
This essay has been developed in arder to investigate the personal changes from adult and young students coursing a night suppletive, and also the reasons implied by them in these changes. The research was conducted in a public school located at the suburbs in São Paulo.There were 33 students from age 15 to 53 ali coursing the 4th grade - Elementary. The main source of the information gathered was a questionary. A group interview wasalso used. The data collected from the student's interviews was separated in different categories upbringing 2 themes: the personal changes related to the adult and young students and the reasons for these personal changes. The theorical considerations which guided the analysis and discussions pointed out in these essay were based in the psychological theory by Henri Wallon. The adult and young students indicate the personal changes and relate them to their school frequency, their acquaintanceship with class-fellows and the satisfaction uponfamily values